Ultrasound‐Guided Cryoablation of a Traumatic Hip Disarticulation Neuroma. Issue 7 (30th December 2016) - Ramsook, Ryan R.; Spinner, David
Abstract: Objective: Traumatic amputation at the pelvic level is a rare procedure with few studies addressing long‐term complications. Painful neuroma formation may form at the site of nerve transection and cause significant impairments in daily living. Ultrasound‐guided cryoablation therapy has grown in popularity and should be considered in patients with painful neuromas. This is a case report of complete pain relief in a patient with rare traumatic hip disarticulation with neuroma formation, treated with ultrasound‐guided cryoablation. The patient gave consent for publication. Design: Single case report. Setting: Mount Sinai Medical Center. Patient: A 57‐year‐old man with traumatic hip disarticulation over 30 years ago with a 10‐year history of severe residual limb pain from neuroma formation. Interventions: Ultrasound‐guided cryoablative injection therapy. Outcome Measures: Pain reduction. Results: Ultrasound‐guided cryoablation of a traumatic hip disarticulation neuroma resulting in complete pain relief and improved functionality and independence. Conclusions: This case illustrates a rare incidence of painful neuroma formation in a patient with traumatic hip disarticulation. Cryoablation with ultrasound guidance resulted in resolution of all pain. We report, to the best of our knowledge, the first occasion of an ultrasound‐guided cryoablation resulting in complete pain relief in a traumatic hip disarticulation neuroma.